Penetapan Kadar Kofein Daun Kopi Kawa ( Coffea Robusta ,Lind ) - Roslinda Rasyid; Winaldi Fitra Sanjaya; Zulharmita Zulharmita (STIFARM Padang, 2013)
Research has been done on the determination of caffeine that leaves Kawa Coffee ( Coffea robusta Linden ex DE Wildem ) by using Soxlhetation method. Coffein from extraction purified by preparative TLC mobile phase solution chloroform : methanol ( 9:1 ).The constration of pure Coffein from preparative TLC has been determinedby using Spectrophotometer Uv-Vis T -70 .The result Coffea Kawa leaves (Coffea robusta Limden ex De Wildem ) is 0.7 % w/w